A comparison of the pro-inflammatory, NF-κB-dependent cytokines: TNF-alpha, IL-1-alpha, IL-6, and IL-8 in different oral fluids from oral lichen planus patients - Rhodus, Nelson L.; Cheng, Bin; Myers, Sandra; Bowles, Walter; Ho, Vu; Ondrey, Frank (Clinical immunology (Orlando, Fla.), 2005)
To explore the feasibility of detection of the level of NF-κB-dependent cytokines in oral fluids from patient with oral lichen planus (OLP) for clinical application, 13 OLP subjects were enrolled in the study as were 13 age–sex-matched controls. In each subject, the whole unstimulated saliva (WUS), mixture of saliva and isotonic saline oral rinse (Saliva-NaCl), and lesion tissue transudates (TT) were collected by standard techniques. The level of cytokines, TNF-alpha, IL-1-alpha, IL-6, and IL-8 in three types of oral fluids was determined by ELISA. In the three types of oral fluids, a significantly higher level of these cytokines was detected in OLP patients than in normal controls. These results indicate that NF-κB-dependent inflammatory cytokines may be detected at increased levels in certain oral fluids which may have diagnostic and prognostic potential for monitoring disease activity and making therapeutic decisions in patients with OLP.